To What Extent Do Fluorophores Bias the Biological Activity of Peptides? A Practical Approach Using Membrane-Active Peptides as Models - Cavaco, Marco; Pérez-Peinado, Clara; Valle, Javier; Silva, Rúben D. M.; Correia, João D. G.; Andreu, David; Castanho, Miguel A. R. B.; Neves, Vera (Frontiers in Bioengineering and Biotechnology, 2020)
The characterization of biological active peptides relies heavily on the study of their efficacy, toxicity, mechanism of action, cellular uptake, or intracellular location, using both in vitro and in vivo studies. These studies frequently depend on the use of fluorescence-based techniques. Since most peptides are not intrinsically fluorescent, they are conjugated to a fluorophore. The conjugation may interfere with peptide properties, thus biasing the results. The selection of the most suitable fluorophore is highly relevant. Here, a comprehensive study with blood brain barrier (BBB) peptide shuttles (PepH3 and PepNeg) and antimicrobial peptides (AMPs) (vCPP2319 and Ctn[15-34]), tested as anticancer peptides (ACPs), having different fluorophores, namely 5(6)-carboxyfluorescein (CF), rhodamine B (RhB), quasar 570 (Q570), or tide fluor 3 (TF3) attached is presented. The goal is the evaluation of the impact of the selected fluorophores on peptides performance, applying routinely used techniques to assess cytotoxicity/toxicity, secondary structure, BBB translocation, and cellular internalization. Our results show that some fluorophores significantly modulate peptides activity when compared with unlabeled-peptides, being more noticeable in hydrophobic and charged fluorophores. This study highlights the need for a careful experimental design for fluorescently labeled molecules, such as peptides.